A relação entre o pensamento moral da justiça e o pensamento moral do perdão - Abreu, Eloá Losano de (2013)
The moral development of forgiveness has been studied since the 1980s by Robert Enright. This author considers forgiveness a moral virtue that develops within the justice, and that depends on it to occur. Although the literature review indicates that justice and forgiveness are positively associated, and that forgiveness allows the emergence of a more compassionate justice, there are no empirical studies that address the relationship between reasonings of justice and forgiveness, especially in the approach of Psychology of Moral Development. Accordingly, the objective of this study was to examine empirically the relationship between the moral reasoning of justice and the moral reasoning of forgiveness. As main theoretical orientation was used the stage model of forgiveness reasoning developed by Enright, Santos and Al-Mabuk (1989), which shows six stages of forgiveness reasoning related to the stages of moral reasoning of justice given in Kohlberg's theory (1984). The study included 155 students, divided into three age groups: pre-adolescents (10 to 14 years), adolescents (15 to 19 years) and young adults (20 to 24 years). As a measure, a questionnaire composed of two moral dilemmas was used, the first to identify the stages of dominant reasoning of justice and the second aimed to identify the dominant stages of forgiveness reasoning. The results showed that the use of stage 4 of justice was the prevailing thought in the three age groups. With regard to forgiveness, pre-adolescents had higher frequency in stage 3, while adolescents and young adults showed mostly stage 4 of thought. It was proven by means of a Wilcoxon test, a relationship of necessity between the reasoning of justice and forgiveness where justice precedes forgiveness in development. In this sense, the stages of forgiveness were always less than or equal to the stages of justice in the participant s thinking. Thus, the results of this study provide important contributions to the field of study on forgiveness and justice in Psychology. The proof that these two thoughts are associated has implications for future research, especially for studies in moral education with a view to development. However, an unbalanced relationship was indentified, where the stages of justice were higher than the stages of forgiveness. It is necessary to investigate the causes of this imbalance and develop strategies to reverse this process.